2017
DOI: 10.1155/2017/6034692
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin Reduces Kidney Damage against BDE‐47‐Induced Apoptosis via Inhibiting NOX2 Activity and Increasing Nrf2 Activity

Abstract: 2,2,4,4-Tetrabromodiphenyl ether (BDE-47), one of the persistent organic pollutants, seriously influences the quality of life; however, its pathological mechanism remains unclear. Troxerutin is a flavonoid with pharmacological activity of antioxidation and anti-inflammation. In the present study, we investigated troxerutin against BDE-47-induced kidney cell apoptosis and explored the underlying mechanism. The results show that troxerutin reduced renal cell apoptosis and urinary protein secretion in BDE-47-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 53 publications
(54 reference statements)
5
25
0
Order By: Relevance
“…As shown by our study, TRX treatment (100 mg/kg) reverses the 5-FU-induced increase of MDA levels and prevents GSH consumption in mice. The antioxidant effect of TRX shown in the present study has also been reported by several published studies in different experimental models [17][18][19]21,[57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown by our study, TRX treatment (100 mg/kg) reverses the 5-FU-induced increase of MDA levels and prevents GSH consumption in mice. The antioxidant effect of TRX shown in the present study has also been reported by several published studies in different experimental models [17][18][19]21,[57][58][59][60][61].…”
Section: Discussionsupporting
confidence: 90%
“…Troxerutin (TRX) is a semi-synthetic flavonoid, derived from rutin, which is extracted from Dimorphandra gardneriana. This compound has various pharmacological activities, including antioxidant [17][18][19], anti-inflammatory [20], anti-apoptotic [21,22], and antiedematogenic [23,24]. Further, it is a potent therapeutic agent for neuropathic pain [25].…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, the levels of NRF-2 increased, suggesting that PBDEs exposure was able to activate the NRF-2 response in SAF-1 cells, probably via oxidative stress. Our observations agree with other works that reported the upregulation of NRF-2 via oxidative stress after PBDEs exposure, both in vivo [85] and in vitro [57,86].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study showed that oxidative stress induces mitochondrial apoptosis, which in turn leads to kidney injury [ 61 ]. To determine whether acute stress induced kidney injury by activating the mitochondrial apoptosis pathway, follow-up studies were performed.…”
Section: Discussionmentioning
confidence: 99%